Estrutura e dinâmica de populações de Hydrochoerus hydrochaeris (Linnaeus, 1766) (Rodentia) em duas áreas urbanas no norte do Paraná, Brasil - Silva, Camila Ferreira da (2015)
This study aimed to evaluate the population ecology of Hydrochoerus hydrochaeris (Linnaeus, 1766) in two urban areas in the north of Paraná, an open and other protected by assessing the effects of these two different types of environments on the structure and dynamics of the population and its implications for conservation of the species. The monitoring of the populations were performed monthly between June 2014 and March 2015 in Jaboti Lake Park (Apucarana / PR) and Conservation Unit Parque Arthur Thomas (Londrina / PR). To conduct the survey population data was used the methodology of total census (direct counting of individuals).They were evaluated ecological parameters of the populations of capybaras, such as ecological density, abundance, age distribution and birth rate, as well as performed the analysis of the landscape. It was applied to analysis of variance (ANOVA) to test the differences between the averages of the abundance of each age group per year of observation, as well as the differences between the average ecological density over the years of observation. The standard relationship between the use of classes and land use in the landscape and the ecological parameters of the capybara populations was evaluated by Principal Component Analysis (PCA). The trend of variation of average abundance over time to Thomas Arthur Park revealed abrupt decrease of the population in a short period of time (2014 16 ± 9, 14 ± 1 and 2015 7±1) as well as ecological density in 2015 (0.05 ind./ha). On the other hand, the Jaboti Lake Park, showed an increase in absolute abundance, with marked recovery of the population in the same period (2014 38±8,30 and 2015 45±1,73) and coming up with an ecological density in 2015 (2 ind ./ha). The birth rate found Lake Park Jaboti was superior to Arthur Thomas Park, which had a negative rate between 2012 and 2015. The use and land cover analysis showed significant differences from the point of view of the relative contribution of landscape elements in the spatial heterogeneity. Arthur Thomas Park shows areas of dense vegetation and urban areas relatively higher than those observed in Jaboti Lake Park that revealed relatively higher proportions of the areas of agriculture / field and exposed soil. Thus, the present study revealed that the local population structure is directly related to the spatial characteristics of both studied landscapes, as can be seen by the greater abundance and density seen in Jaboti Lake Park compared to Arthur Thomas Park in recent years of study.